The Crop Coefficient of Barley (Hordium vulgare) Under Gezira Conditions (University of Khartoum Journal of Agricultural Sciences, 2023)
The development of regionally based and growth-stage-specificcrop coefficient Kc helps in estimation of the crop water requirements(CWR) and irrigation planning. In this regard the Kc of barley is needed forthe estimation of CWR in the Gezira and similar regions in the Sudan. Anexperiment was conducted for three consecutive seasons 2003/04, 2004/05and 2005/06, at Gezira Research Station to determine the Kc of barley. Thecrop evapotranspiration (ETc), reference crop evapotranspiration (ET0 ) andthe crop coefficient values as ratios of ETc to ET0 were calculated. Theresults showed that the Kc values of 0.48, 0.96, 1.04 and 0.48 wereappropriate for the initial stage, crop development, and mid-season and lateseason stages, respectively. These Kc values could be used for estimation ofCWR as a product of Kc * ET0 in the Gezira as well as other similar regionsof the Sudan.